The complete mitochondrial genome of Taiwan slug-eating snake (Pareas formosensis) and phylogenetic analysis. Issue 11 (2nd November 2021) - Liu, Yan-Lin; Zhang, Ya-Jun; Yang, Xian; Yang, Xiao-Xiang; Lin, Zhi-Hua; Ma, Li
Abstract: We report the complete mitochondrial genome (mtDNA) of Pareas formosensis (Squamata: Colubridae). This circular mtDNA is 17, 703 bp in size and consists of 13 protein-coding genes, 22 transfer RNAs, 2 ribosomal RNAs, and 2 non-coding sequence (D-loop). The total of mtDNA was composition of 57.26% A + T and 42.74% G + C (T: 25.21%, C: 28.84%, A: 32.05%, G: 13.90%). The phylogenetic analysis revealed that P. formosensis formed a clade with other species of Pareas . This mtDNA sequence of P. formosensis provides useful data for studying the population genetics and phylogeography of Colubridae.